Extensive Reading as a Gateway to Create Research Gap: Valuable Lessons from Indonesian Expert Authors - Fahrus Zaman Fadhly (Indonesian Journal of EFL and Linguistics, 2022)
Identifying research gaps from the extensive reading process is an inevitable choice for researchers in any field. This study aims to explore various approaches in identifying research gaps that have the potential to become elements of novelty. By using a grounded theory approach, the research reconstructs the cognitive experiences of a number of Indonesian expert authors in identifying research gaps. The results show that scientific journals as the primary source are accessed from the subscription data center; discuss and conduct knowledge sharing with expert groups; bibliography mapping by establishing a basic reference to avoid getting out of the focus of the research topic; state of the art and novelty elements will be seen from the extensive reading; using software to synthesize the literature review. It concludes that the research gap as the forerunner of the novelty element can only be done through an extensive reading process. Through extensive reading allows researchers or scientific writers to find many research gaps that can be explored.